Long-term Safety of Pregnancy Following Breast Cancer According to Estrogen Receptor Status. (26th October 2017) - Lambertini, Matteo; Kroman, Niels; Ameye, Lieveke; Cordoba, Octavi; Pinto, Alvaro; Benedetti, Giovanni; Jensen, Maj-Britt; Gelber, Shari; Del Grande, Maria; Ignatiadis, Michail; de Azambuja, Evandro; Paesmans, Marianne; et al.
Abstract: Safety of pregnancy in women with history of estrogen receptor (ER)–positive breast cancer remains controversial. In this multicenter case–control study, 333 patients with pregnancy after breast cancer were matched (1:3) to 874 nonpregnant patients of similar characteristics, adjusting for guaranteed time bias. Survival estimates were calculated using the Kaplan-Meier analysis; groups were compared with the log-rank test. All reported P values were two-sided. At a median follow-up of 7.2 years after pregnancy, no difference in disease-free survival was observed between pregnant and nonpregnant patients with ER-positive (hazard ratio [HR] = 0.94, 95% confidence interval [CI] = 0.70 to 1.26, P = .68) or ER-negative (HR = 0.75, 95% CI = 0.53 to 1.06, P = .10) disease. No overall survival (OS) difference was observed in ER-positive patients (HR = 0.84, 95% CI = 0.60 to 1.18, P = .32); ER-negative patients in the pregnant cohort had better OS (HR = 0.57, 95% CI = 0.36 to 0.90, P = .01). Abortion, time to pregnancy, breastfeeding, and type of adjuvant therapy had no impact on patients' outcomes. This study provides reassuring evidence on the long-term safety of pregnancy in breast cancer survivors, including those with ER-positive disease.